Perancangan Media Siap UN Matematika SMP Berbasis Android - Mugi Jayanti; Yogi Wiratomo (SAP (Susunan Artikel Pendidikan), 2017)
Students’ habitof using electronic devices for games and social media can reduce the education quality, as seen in the less satisfactory results of Junior High School National Examination. To improve this result, it is necessary to give students more exercises while considering their habit of using electronic devices. This research aims to develop an android-based educational medium for practicing doing National Examination questions for Junior High School Studentsand to determine its eligibility based on validation and evaluation by subject experts, media experts and practitioners of mathematics learning. The type of the research is research and development performed based on the development model ADDIE (Analysis, Design, Development, Implementation, Evaluation),but only conducted until the fourth stage (implementation). Media validation is conducted by subject experts, media experts and practitioners of mathematics learning in MTs (Madrasah Tsanawiyah). Data are collected by distributing a questionnaire and then analyzed descriptively, qualitatively and quantitatively. The result show sthe android-based medium “Siap UN SMP” is very suitable to use as a medium for practicing doing questions of National Examination at Junior High School Level.